2018
DOI: 10.22219/jpbi.v4i2.5889
|View full text |Cite
|
Sign up to set email alerts
|

Research methods and data analysis techniques in education articles published by Indonesian biology educational journals

Abstract: The essential of studies which focus on research methods in biology educational field is providing recommendations for the next researchers the proper methods they need to use. Unfortunately, this kind of research is still hard to find in Indonesia. The aim of this study was to access the diversity of research approaches, designs, variables, data collection and analysis techniques, as well as research subjects in the articles published in Indonesian biology educational journals throughout 2017. Content analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 32 publications
4
27
0
8
Order By: Relevance
“…On the other hand, various researchers in Indonesia have conducted various researches to seek the solution to overcome various problems of biology learning. Various research designs and methods were used in the various studies (Fauzi & Pradipta, 2018). In relation to the many concepts that must be studied on various biological courses, some previous research reports have also reported and recommended the use of some learning models (Buku, Mite, Fauzi, Widiansyah, & Anugerah, 2015;Fauzi, 2013;Fauzi & Ramadani, 2017;.…”
Section: The Courses In the Biology Department Are Often Chosen To Bementioning
confidence: 99%
“…On the other hand, various researchers in Indonesia have conducted various researches to seek the solution to overcome various problems of biology learning. Various research designs and methods were used in the various studies (Fauzi & Pradipta, 2018). In relation to the many concepts that must be studied on various biological courses, some previous research reports have also reported and recommended the use of some learning models (Buku, Mite, Fauzi, Widiansyah, & Anugerah, 2015;Fauzi, 2013;Fauzi & Ramadani, 2017;.…”
Section: The Courses In the Biology Department Are Often Chosen To Bementioning
confidence: 99%
“…Educational development should be able to accommodate the optimization of students' critical thinking skill empowerment (Strauss, 2016). The development itself cannot be separated from a number of studies that have contributed to providing plentiful discussions about sustaining quality improvement on instructional process (Fauzi & Pradipta, 2018;Spencer-rodgers & Cortijo-ocaña, 2015). Some studies, also, have strained to uncover the level of students' critical thinking skill in search of potential attempt for optimization of critical thinking empowerment during instructional activities (Huber & Kuncel, 2016;Tiruneh, Verburgh, & Elen, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…An experimental design is a traditional approach to conducting quantitative research (Creswell 2015). In short, researchers use experimental research to compare two or more groups on one or more measures.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental designs are used in this way to answer hypotheses. According to Creswell (2015), experimental research is a study to test an idea, practice, or procedure to determine whether to affect the outcome or dependent variable. Furthermore, the experiment was used when wanting to establish the possible causes and effects between the independent variables and the dependent variable.…”
Section: Introductionmentioning
confidence: 99%